2018
DOI: 10.33102/jfatwa.vol10no1.28
|View full text |Cite
|
Sign up to set email alerts
|

Lokalisasi Unit Zakat Institusi Pengajian Tinggi Sebagai Model One Stop Center Agihan Zakat Pendidikan

Abstract: The issue of decentralization and localization of zakat administration is essential in improving the efficiency of the distribution of zakat in Malaysia. This study was motivated by the hypothesis that the implementation of the localization of zakat administration is expected to provide a significant and positive impact as a 'One Stop Center' to asnaf students poor (fakir) and needy (miskin). This study attempts to solve the problem and identify the needs of students in line with the principles outlined zakat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Availability and accessibility to information communication technology or information and communication technology (ICT) resources are essential to ensure the zakat recipient can gather enough information about zakat and subsequently make their zakat assistance application from the zakat website (Ahmad Razimi et al , 2016). Jalil et al (2015) suggested the concept of a “one-stop centre” to be implemented upon zakat distribution in HLIs. The one-stop centre serves as an information, meeting point and recreation centre.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Availability and accessibility to information communication technology or information and communication technology (ICT) resources are essential to ensure the zakat recipient can gather enough information about zakat and subsequently make their zakat assistance application from the zakat website (Ahmad Razimi et al , 2016). Jalil et al (2015) suggested the concept of a “one-stop centre” to be implemented upon zakat distribution in HLIs. The one-stop centre serves as an information, meeting point and recreation centre.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agihan zakat pendidikan memainkan peranan kelas pertama kepada asnaf untuk memperoleh pendidikan dan mengubah nasib mereka. Ini bertujuan untuk meningkatkan kecemerlangan mental, fizikal dan rohani pelajar (Muhammad Rizal, Hairunnizam & Sanep, 2017) dan mempengaruhi kualiti hidup mereka untuk memerdekakan diri daripada lingkaran kemiskinan (Hairunnizam, Sanep & Mohd Ali, 2004). Pelaksanaan agihan zakat pendidikan di peringkat IPT dilihat dapat mengurangkan proses birokrasi dalam permohonan dan agihan bantuan zakat selain memudahkan pelajar untuk berkomunikasi dengan wakil zakat (Mohd Faiz et al, 2016).…”
Section: Skim Agihan Zakat Pendidikan Kepada Asnaf Pelajarunclassified
“…Pelaksanaan agihan zakat pendidikan di peringkat IPT dilihat dapat mengurangkan proses birokrasi dalam permohonan dan agihan bantuan zakat selain memudahkan pelajar untuk berkomunikasi dengan wakil zakat (Mohd Faiz et al, 2016). Ini kerana pihak universiti lebih mengenali kelayakan dan keperluan pelajar mereka serta lebih memahami keadaan pembelajaran dan kos sara hidup pelajar mereka (Muhammad Rizal, Hairunnizam & Sanep, 2017;Dicky Wiwittan, Hairunnizam & Mohd Ali, 2016).…”
Section: Skim Agihan Zakat Pendidikan Kepada Asnaf Pelajarunclassified